On Extendability of Solutions of Differential Equations to a Singular Set - Kaplun, Yu. I.; Samoilenko, V. G. (Ukrains’kyi Matematychnyi Zhurnal, 2003)
We consider the problem of the extendability of solutions of differential equations to a singular set that consists of points at which the right-hand side of the equation considered is undefined.